The periodisation of ceramic production in Thrace during the Roman period (1st–4th centuries) - Kabakčieva , Gergana (Balcanica Posnaniensia. Acta et studia, 1990)
The article analyzes the problem of the periodization of ceramic production in Thrace in the Roman period. The problem is significant for studies on economic and cultural transformations of the region under the influence of romanization. The aim of the work is to distinguish the main stages of ceramic development and characterize them. The author applies analysis of archaeological material, including forms, technology, and context of finds. The most important results indicate three main periods of development: from the 1st to the beginning of the 2nd century AD, from the 2nd to the mid-3rd century, and from the mid-3rd to the 4th century AD. In the first period, coexistence of traditional Thracian ceramics and Roman influences is observed; in the second, domination of mass production of terra sigillata; and in the third, a transition to early Byzantine forms. The analysis also shows the importance of influences from Asia Minor and the development of local workshops. The conclusion is that ceramic production in Thrace reflects processes of romanization while preserving elements of local tradition.